Chemical Constituents and Biological Activity of Kaempferia Angustifolia, K. Rotunda,Spermacoce Articularis and S. Exilis - Neoh, Bee Keat (2006)
Kaempferia angustifolia, K rotunda (Zingiberaceae), Spennacoce articularis and S. exilis (Rubiaceae) were chosen since they have long been used traditionally in medicinal treatment. In this research, isolation and separation work had been carried out using various solvents and chromatographic methods. The structure of these compounds were determined by using spectroscopic methods such as ineared (IR), nuclear magnetic resonance ('H, 13C and 2D- NMR), mass spectrometry (MS) and by comparison with the data reported previously. The crude extracts and some of the isolated compounds were subjected to the biological activity test: antioxidant, antimicrobial tests, cytotoxic screening and larvicidal activity.Extracts fiom Kaempferia angush~oliah ave yielded a new compound angustifolienol (58), together with seven other compounds; crotepoxide (33), p-sitosterol (a), boesenboxide (M), 2'-hydroxy-4, 4', 6'-trimethoxychalcone (Xi), 6-methylzeylenol (59), and sucrose (60), and zeylenol(35). Frationation of extracts fiom K. rotunda has yielded five pure compounds; crotepoxide (33), tetracosanoic acid (61), benzoic acid (62), stigmasterol (45) and p-sitosterol (44). Both tetracosanoic acid (61) and benzoic acid (62) are new to species. Extracts fiom S. art'iculm's gave two pure compounds, identified as ursolic acid (63) and stigmasterol (45). While the extracts from S. exilis gave four compounds, benzo[g]isoquinoline-5,IOdione (64), stigmasterol (49, hexadecanoic acid (65) and ursolic acid (63). Phytochemical studies on later species had never been reported before. Acetylations of new compound, angustifolienol (58) gave two derivatives, triacetoxyangustifolienol (66) and diacetoxyangustifolienol (67). Both are new compounds, and have never been reported previously either as natural product or synthesized compounds. The major constituents of the essential oil of K. angustifolia was DL- camphor (20.57 %), while the major constituent of K. rotunda was benzyl benzoate (49.84 %). The major constituent of the essential oil of S. articularis was phytol(10.31 %), while the major constituent of S. exilis was oleic acid (20.9 %).Cytotoxic screening showed that all the crude extracts of K angustiijolia and K. rotunab were not cytotoxic against HL-60 cell line. However, pure compounds of K. angu~hyolia showed strong activity. All crude extracts of S. articularis and S. exilis (except hexane extract of S. exilis) and ursolic acid (63) were strongly cytotoxic towards HL-60 and MCF-7 cell lines. All extracts and most of the pure compounds were subjected to four strains of microbes (MRSA, Pseudomonas aeruginosa, Salmonella typhimurium and Bacillus subtilis) in the antimicrobial test. Pet. ether extracts fiom Kaempferia species, all extracts fiom S. exilis and boesenboxide (34) were active towards some microbes. In antioxidant assay, K rotunda was more active than Kaempferia angustiyolia while both Spennacoce species were moderately active. Besides that, some of the compounds from Kaempferia angustzyolia were subjected to the antioxidant assay and showed stronger antioxidant activity than a- tocopherol. In addition, all plants also showed moderate to low larvicidal activity.